Mechanical and thermal properties of high-density polyethylene/alumina/glass fiber hybrid composites. (November 2019) - Lins, Sergio Augusto B; Rocha, Marisa Cristina G; d'Almeida, José Roberto M
In this investigation, composite materials made from high-density polyethylene (HDPE) and alumina, as well as from HDPE, alumina, and glass fibers, were prepared, aiming to improve the thermal stability, stiffness, and mechanical strength. The combined effects of alumina and glass fibers and the individual effects of alumina were studied. Alumina concentrations ranged from 5 wt% to 10 wt% and glass fiber concentrations ranged from 10 wt% to 30 wt%. For the hybrid composite materials, alumina concentration was maintained constant as the glass fiber concentration increased. The composites were processed with a double-screw extruder. Their properties were evaluated through a multi-analytical approach. Results pointed to a significant increase of the elastic modulus for the hybrid composite (up to 501% in comparison to the neat polymer), at the cost of a large decrease in toughness, alongside a decline in impact resistance. Elastic modulus improvement was observed in both hybrid and HDPE-alumina composites, being higher for the hybrid composites due to the addition of glass fibers. HDPE-alumina composites presented a decrease in mechanical strength, whereas the hybrid composites showed an increase of this parameter. Concerning thermal properties, the hybrid composites presented higher thermal stability than that of the HDPE-alumina composites and a similar degradation temperature as the neat polymer. Micrographs pointed to weak adhesion between alumina particles and the polymeric matrix as well as a slight degree of fiber detachment. Overall, the hybrid composites presented considerably higher stiffness and mechanical strength than the neat polymer and HDPE-alumina composite (19–26% increase), with no significant change in thermal stability.